Advancing patient-centered care through transformative educational leadership: a critical review of health care professional preparation for patient-centered care - Lévesque MC; Hovey RB; Bedos C (Dove Medical Press, 2013)
Martine C Lévesque,1,2 Richard Bruce Hovey,2,3 Christophe Bedos2,4 1Faculté de médecine, Université de Montréal, Montréal, QC, Canada; 2Division of Oral Health and Society, Faculty of Dentistry, McGill University, Montreal, QC, Canada; 3Faculty of Medicine, University of Calgary, Calgary, AB, Canada; 4Département de médecine sociale et préventive, Faculté de médicine, Université de Montréal, Montréal, QC, Canada Abstract: Following a historical brief on the development of patient-centered care (PCC), we discuss PCC's value and role in counterbalancing the evidence-based movement in health care. We in turn make a case for a philosophical shift in thinking about the PCC concept, one based on a consideration for how knowledge is produced, used, and valued within care provision processes. A “shared epistemology” foundation is presented, defined, and promoted as essential to the authentic and ethical realization of “shared decision making” between patient and health care provider, and, more generally, of PCC. In accordance with these views, this article critically reviews the literature on health care professional education for the development of PCC. We uncover the disturbing ways in which education frequently undermines the development of patient centeredness, despite curricular emphasis on professionalism and ethical PCC. We also establish the need to raise awareness of how dominant approaches to evaluating student or practitioner performance often fail to reinforce or promote patient centeredness. Finally, we identify successful and inspiring cases of teaching and learning experiences that have achieved perspective transformation on PCC and on new ways of providing care. The pertinence of adopting the theoretical foundations of adult transformative learning is argued, and a call to action is proposed to the leadership of health professional educators across all disciplines. Keywords: patient-centered care, health professional education, transformative learning